THE CONSEQUENCES OF POLITICAL ACCOMONDTION ON POLITICAL STABILITY IN DEVELOPING COUNTRIES - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This research project is aim to tackles the issues regarding the impact of the political accommodation in the political stability in South Sudan, the study is conducted in Central Equatoria State in Juba the capital city of South Sudan. The research is pointing out the issues affecting political stability in South Sudan and the possible solution to remedy the problem which is highlighted throughout the research. The research outlines all the problem that face the political system in South Sudan and also compares to the other countries to find out how these countries carry out their political accommodation for the political stability in their governments. The researcher’s aim is that this research will help the government in South Sudan for the establishment of the stable political system in South Sudan. The literature review point out relevant literature from books and other credible sources of information that the researcher uses to highlight grievances in the political system in South Sudan and other political institution and those concerned. In its subsequent chapters the design used is highlighted research data questionnaires, interviews and observation and among others. The researcher sum up the research and conclude with possible solution for political stability in South Sudan. The finding traced out cause of political instability in South Sudan back to policy of political accommodation adopted by government as a method of putting to end the political dispute in the country. It was also believed that lack of accountability on constitutional post holders and entire government workers at different level of capacities had also contributed to be cause of instability among others in the country. Majority of the respondents believed that from 2005 to the mid of 2012, the political situation was stable and country was growing faster economically and entire nation was in peace. The political instability started in 2013 when political disputes erupted out from ruling Party members (Sudan’s People Liberation Movement) which later escalated to be conflict creating political chaos and mess in ruling system of the country. The attempt made by government to settle political dispute among different parties by using political accommodation had negatively been understood by some politicians and military commanders to be chance of hunting positions in the government through rebellion. Some of politicians resorted to policy of grasping power through unconstitutional mean such as military coup, tribal conflicts incitement and economic war instead of democratic mean of power transfer.